Safety Drill Evacuation Using Virtual Reality in Universiti Teknologi PETRONAS - Samsudin, Aryssa Sofea (IRC, 2019)
Safety drill evacuation is important for every building and evacuation plan is necessary to make it happen. Through the evacuation plan, the evacuees able to escape the building using the escape road map purposed in the evacuation plan. Few factors and theories that related to safety evacuation model and human behavior are identified which can delay the time for evacuees to escape or the evacuees will experience an extreme panic state which can affect them mentally and physically. In a university, the number of private hostels is to support the number of students that keeps increasing. Thus, the probability of fire risk is high when the number of people is high. Student awareness of the evacuation plan is a concerning issue. Some students even ignore the fire drill alarm. Therefore, a simulation using virtual reality (VR) is purposed for the safety drill. VR provides simulation to experience the real-life environment by giving a concept of an immersive environment and to interact with 3D worlds virtually instead of viewing a screen. Using simulation, the user or the potential evacuees will experience a real-time fire accident virtually. Through the simulation, the user trained on how to handle the situation when a fire accident happens and help users to memorize the escape road map. By using Unity software to develop the simulation where it can help to design the fire accident scenarios and virtual reality headset for the user to experience the immersive environment virtually. This project using Rapid Application Development (RAD) to develop the simulation drill. The safety drill evacuation simulation comprises two modules which are a walk-through simulation module and a game module to test the user's ability to evacuate the building.